2016
DOI: 10.1371/journal.pone.0156304
|View full text |Cite
|
Sign up to set email alerts
|

Priority Setting and Influential Factors on Acceptance of Pharmaceutical Recommendations in Collaborative Medication Reviews in an Ambulatory Care Setting – Analysis of a Cluster Randomized Controlled Trial (WestGem-Study)

Abstract: BackgroundMedication reviews are recognized services to increase quality of therapy and reduce medication risks. The selection of eligible patients with potential to receive a major benefit is based on assumptions rather than on factual data. Acceptance of interprofessional collaboration is crucial to increase the quality of medication therapy.ObjectiveThe research question was to identify and prioritize eligible patients for a medication review and to provide evidence-based criteria for patient selection. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 45 publications
1
26
0
2
Order By: Relevance
“…Furthermore, in our study, the type and number of implemented pharmaceutical recommendations affected the observed change in the quality of medication therapy. The process evaluation yielded a mean implementation rate of pharmaceutical suggestions of 54.9%; the rate increased the longer physician and pharmacist had been cooperating (33). The identified number of drugrelated problems corresponds to comparable studies (34,35).…”
Section: Results In the Context Of The Published Literaturementioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, in our study, the type and number of implemented pharmaceutical recommendations affected the observed change in the quality of medication therapy. The process evaluation yielded a mean implementation rate of pharmaceutical suggestions of 54.9%; the rate increased the longer physician and pharmacist had been cooperating (33). The identified number of drugrelated problems corresponds to comparable studies (34,35).…”
Section: Results In the Context Of The Published Literaturementioning
confidence: 79%
“…Larger followup studies should adapt the intervention to a wider and optimized community setting. The authors' own secondary analyses demonstrated, for example, that not all patients benefitted equally from participating in medication management (33). In view of the resource implications associated with the interdisciplinary management of patients, criteria for how to select suitable patients might be conceived.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is inconsistency within Canada, and internationally, regarding what this service typically entails. 41 The goals of medication review programs in some Canadian provinces are to confirm an individual patient’s medication list and to help them to better understand their medications. Medication review programs in other provinces go further and require pharmacists to assess the indication, efficacy, safety, and convenience of the patient’s medications to identify drug therapy problems and make care plans to optimize health outcomes, in collaboration with the other care providers (e.g., Comprehensive Care Plans in Alberta).…”
Section: Primary Care Services Offered By Community Pharmaciesmentioning
confidence: 99%
“…The MAI‐change is strongly related to pre‐interventional appropriateness: the higher the MAI at baseline the higher the mean reduction. A MAI‐baseline‐score ≥24 was identified as a possible cut‐off value to initiate a medication review . In clinical practice the MAI could be used to pre‐assess whose medication needs to be assessed and which patients potentially benefit from a medication review.…”
mentioning
confidence: 99%